Knowledge and Practices Regarding Personal Listening Device Use and Associated Health Risks among Medical Students - Rizka Fakhriani; Asti Widuri; Danu Yudistira (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: The growing use of personal listening devices (PLDs) among young adults has raised concerns about unsafe listening practices, yet evidence on Indonesian medical students’ knowledge remains limited. This study aimed to assess undergraduate medical students’ knowledge of hearing-related risks and self-reported PLD listening practices. Methods: An analytical cross-sectional study was conducted among undergraduate medical students at a university in Yogyakarta, Indonesia, from April to May 2022. A total of 182 students completed a structured self-administered questionnaire adapted from previous studies. The questionnaire covered demographic characteristics, knowledge of hearing-related risks, and safe listening practices. Chi-squared or Fisher’s exact tests were used to examine associations between categorical variables, with statistical significance set at p < 0.05. Results: Most respondents (76.4%) had used PLDs for more than five years. Nearly half (49.5%) reported using PLDs for less than one hour per day, and 39.0% preferred a loud listening volume. Most participants recognised possible consequences of prolonged PLD use, including hearing loss (100%) and tinnitus (99.5%). Overall, 61.5% identified less than three hours as the safe limit at normal volume, and 72.0% identified less than one hour at loud volume. Conclusion: Respondents generally recognised hearing-related risks; however, knowledge of safe-listening recommendations and exposure limits was incomplete, and potentially unsafe listening practices were reported. These findings support hearing-conservation education that emphasises practical safe-listening behaviours among university students.